Pengaruh Pelatihan Visual Motor Behavior Rehearsal Terhadap Peningkatan Kepercayaan Diri Atlet - Indra Prasetyo; Fuad Nashori (JIP (Jurnal Intervensi Psikologi), 2009)
This study intends to investigate the effect of visual motor behavior rehearsal training on athletes self confidence. The hypothesis was there are differences in the self confidence level of basketball athletes between experimental group compare to control group after visual motor behavior rehearsal training was given.The subjects of this study were 18 university students aged 18-20 years old or comparatively active in the regulation of PERBASI. The control group were college students that fuse at Universitas Islam Indonesia's basketball unit, and the experimental group were college students that fuse at Universitas Gadjah Mada's basketball unit. Data collected using the self confidence scale by Vealey, which has proven it's reliability and validity. Results showed that there were significant difference in the confidence level of basketball athletes between experimental groups paired to control group after the training was given.Key words: self confidence, visual motor behavior rehearsal training, basketball athletes.